The Problem of Transylvania in the Emigration Correspondence of Count Béla Teleki from the End of the Second World War to the Abolition of the Communist Regime - Murádin János Kristóf (Sciendo, 2021)
The aim of this study is to analyse the voluminous emigration correspondence of Count Béla Teleki in order to highlight his main thoughts about the future of Transylvania. Béla Teleki was one of the most important Transylvanian politicians in the middle of the 20th century. His political career reached its peak at the time when Northern Transylvania was regained by Hungary after the Second Vienna Award. At the end of the Second World War, Teleki was persecuted by the Secret Police of the new Hungarian Communist Regime. Starting from 1951, he lived in the United States until his death on 7 February 1990. During the decades of his life in emigration, he carried on a great correspondence with the leading personalities of the Hungarian emigration in the West, several members of the American Senate, and even with President Gerald Ford. In this way, Béla Teleki became one of the central personalities of the Hungarian emigration in the Western World. His opinion, his voice were determining. This study summarizes the most important theme Béla Teleki was preoccupied with, the future of Transylvania, as he imagined it, by making a short analysis of his correspondence consisting of thousands of letters.